Živalski frazemi v štajerskem južnopohorskem narečju - Zorko, Zinka; Benko, Anja (Slavia Centralis, 2020)
ANIMAL PHRASEMES IN THE STYRIAN SOUTH POHORJE DIALECT The paper discusses the Styrian South Pohorje dialects of Mislinja and Oplotnica. On the phonological level, the Mislinja dialect belongs to the Styrian and not Carinthian dialect as proposed by the maps in Tone Logar and Jakob Rigler’s 1993 Karta slovenskih narečij. Phraseology research as a science on its own started evolving in the 1970s. The feld of animal phraseology deals with the animals living in their domestic as well as other (i. e. wild) environments. The culled animal phrasemes are written in the Oplotnica dialect and collected from the Pleteršnik’s 1894 Slovensko-nemški slovar.